Stabilization and Synchronization of Memristive Chaotic Circuits by Impulsive Control. (5th December 2017) - Zou, Limin; Peng, Yang; Feng, Yuming; Tu, Zhengwen
Abstract : The purpose of this note is to study impulsive control and synchronization of memristor based chaotic circuits shown by Muthuswamy. We first establish a less conservative sufficient condition for the stability of memristor based chaotic circuits. After that, we discuss the effect of errors on stability. Meanwhile, we also discuss impulsive synchronization of two memristor based chaotic systems. Our results are more general and more applicable than the ones shown by Yang, Li, and Huang. Finally, several numerical examples are given to show the effectiveness of our methods.